Sex Workers and the Best Interests of their Children: Issues Faced by Sex Workers Involved in Custody and Access Legal Proceedings - DeWolf, Julie E. (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2021)
Sex worker parents often lose custody of their children. The purpose of this research was to study theimpact of a parent’s status as a past or present sex worker on judicial decision-making in custody and access disputes. Through doctrinal legal research, I explored judicial treatment of sex workers involved in custody and access disputes in Child Protection and Family Law case law from Ontario. I reviewed every reference to parental involvement in sex work from Child Protection and Family Law decisions from January 2010-March 2020. Parental involvement in sex work was often presented as an unfavourable aspect of the parent, or otherwise had a negative influence on their claim. Sex work was treated as a negative quality in a parent rather than an aspect of their life warranting further factual exploration. I argue that stigma against sex workers appears to carry more weight in custody and access disputes than evidence concerning the impact that a parent’s sex work has on a child.